Management and Optimization of Hazards In Working Industries - Rehman Azhar Mohamad Ayazoddin5 Arutl, Mir Munawar Ali, Mohd Aamer Khan Mohammed Shafi Faraz U (International Journal of Scientific Research and Management (IJSRM), 2017)
:Industry isoneofthe oldest,anditisbeing realizedallover the worldthattheindustry has cometooccupyanimportantposition inthe nationaldevelopmentprograms.Moreover, all overthe industry employsaverylargeamountofmanpower.Still,very little attentionhasbeenpaid so fattothedevelopment ofindustryonscientificandorganized lines. Thereisnoworthwhile efforttousethe appropriate technologyin spite ofvastscope, variety,volume of the works, talent and resourcesin the developingcountries. The safety in Industry isone of theimportant measure to be takenbuthassomewhatbeenneglectedin the industry. Unfortunately to some extent,thishappensnotonly at themicrolevel buteven ona macrolevel. It must be accepted that theindustryhastobeoperatedonscientificlines andithastocatertotheeconomicandsocial well-being ofallthoseinvolvedinit.Thestudy includeshow tointroducenew practicesforsafe guardof the workers fromtheworkplacehazardsintheindustry andoptimizing hazards.